Managing short bowel syndrome: Making the most of what the patient still has - Parekh, Neha; Seidner, Douglas; Steiger, Ezra (Cleveland Clinic Journal of Medicine, 2005)
Short bowel syndrome (severe malabsorption after resection of the small bowel) is characterized clinically by chronic diarrhea, dehydration, electrolyte abnormalities, and malnutrition. The severity and management depend on the site and extent of the intestinal resection, whether the ileocecal valve remains, whether there is disease in the residual bowel, and the degree of adaptation of the remaining bowel.